Network monitoring / analysis based on TCP/UDP scanning - Mohd Azhari, Siti Fatimah (2017)
Life become easier with networking. More than 3 billion people in the world be accessed computer network. Number of its user increased in past few years and traffic flows in networks also increased, so it’s very important to monitor networks traffic as well as its user’s activities to keep the network smooth and efficient. Monitoring and analysis became a challenging task due to threats and security issue led by effect increasing changes in the network. However, network monitoring system plays a significant role in the network security and management. Network monitoring refers to the observation on the events, happening through the network with the aim of providing a secure and persistent network. The foremost goal of this project is to observe network traffic on three different place in same period. This project is also to observe IP packet data by way of different allied parameters with simplicity. This project using the Wireshark as software for monitoring and scanning these network is been introduced in this research. Moreover this project also to investigate how many packets sending and receive at one time and one location.